VAT and Agriculture: Lessons from Europe - Sijbren Cnossen (Center for Economic Studies and ifo Institute (CESifo), 2017)
Farmers are often exempted from VAT for administrative and political reasons. But this means that the VAT on their inputs cannot be `washed out' through the tax deduction/credit mechanism. To compensate farmers for the uncompensated VAT on inputs, the EU has devised a flat-rate scheme that permits them to charge a presumptive rate (approximately equal to the effective VAT rate on sector-wide inputs) on their sales to taxable agro-processing firms. The flat-rate scheme is an arbitrary way of trying to achieve equal treatment. Full taxation, subject to the general threshold, appears to be the preferred choice.
Keywords: H22; H25; 330; VAT; agriculture; European union; flat-rate compensation scheme; reduced rates; incidence